Landscapes of ritual performance in Eastern North America - Claassen, Cheryl (American Landscapes, 2023)
"In the long history of documenting the material culture of the archaeological record, meaning and actions of makers and users of these items is often overlooked. The authors in this book focus on rituals exploring the natural and made landscape stages, the ritual directors, including their progression from shaman to priesthood, and meaning of the rites. They also provide comments on the end or failure of rites and cults from Paleoindian into post-DeSoto years. Chapters examine the archaeological records of Cahokia, the lower Ohio Valley, Aztalan Wisconsin, Vermont, Florida, and Georgia, and others scan the Eastern US, investigating tobacco/datura, color symbolism, deer symbolism, mound stratigraphy, flintknapping, stone caching, cults and their organization, and red ochre. These authors collectively query the beliefs that can be gleaned from mortuary practices and their variation, from mound construction, from imagery, from the choice of landscape setting. While some rituals were short-lived, others can be shown to span millennia as the ritual specialists modified their interpretations and introduced innovations"--